Negative Frequency-Dependent Selection Is Frequently Confounding - Brisson, Dustin (Frontiers in Ecology and Evolution, 2018)
Persistent genetic variation within populations presents an evolutionary problem, as natural selection and genetic drift tend to erode genetic diversity. Models of balancing selection were developed to account for the maintenance of genetic variation observed in natural populations. Negative frequency-dependent selection is a powerful type of balancing selection that maintains many natural polymorphisms, but it is also commonly misinterpreted. This review aims to clarify the processes underlying negative frequency-dependent selection, describe classes of polymorphisms that can and cannot result from these processes, and discuss the empirical data needed to accurately identify processes that generate or maintain diversity in nature. Finally, the importance of accurately describing the processes affecting genetic diversity within populations as it relates to research progress is considered.